2017
DOI: 10.1039/c7nr02755a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of nanoporous graphene/polymer composite membranes

Abstract: Graphene is currently investigated as a promising membrane material in which selective pores can be created depending on the requirements of the application. However, to handle large-area nanoporous graphene a stable support material is needed. Here, we report on composite membranes consisting of large-area single layer nanoporous graphene supported by a porous polymer. The fabrication is based on ion-track nanotechnology with swift heavy ions directly creating atomic pores in the graphene lattice and damaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
54
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 28 publications
0
54
0
1
Order By: Relevance
“…This can be achieved by either highly charged or by very fast (swift) heavy ions. For both it has been shown that they can be used for defect engineering of 2D materials such as carbon nano-membranes, 26,27 graphene, [28][29][30][31][32][33] hexagonal boron nitride, 34 and MoS 2 . [35][36][37] Swift heavy ions (SHI) excite target atoms along their trajectory and the corresponding energy deposited per track length into the target material is usually given in terms of electronic stopping power S e = dE/dx.…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved by either highly charged or by very fast (swift) heavy ions. For both it has been shown that they can be used for defect engineering of 2D materials such as carbon nano-membranes, 26,27 graphene, [28][29][30][31][32][33] hexagonal boron nitride, 34 and MoS 2 . [35][36][37] Swift heavy ions (SHI) excite target atoms along their trajectory and the corresponding energy deposited per track length into the target material is usually given in terms of electronic stopping power S e = dE/dx.…”
Section: Introductionmentioning
confidence: 99%
“…However, i) large‐area membrane quality graphene synthesis and transfer to suitable porous supports (without polymer residue or other contamination from transfer), ii) mitigation of nonselective leakage by plugging tears/damages to graphene from transfer and subsequent processing during membrane fabrication, and most importantly iii) the formation of nanopores with a high density and narrow size distribution using cost‐effective, scalable processes are some of the major challenges that need to be collectively addressed to realize NATMs for practical applications . Here, we note that large‐area monolayer graphene synthesis has been demonstrated via roll‐to‐roll chemical vapor deposition (CVD) processes .…”
mentioning
confidence: 97%
“…However, the reproducible formation of sub-nanometer pores in 2D membranes with high pore density remains a challenge. 7,8 Porous 2D membranes are commonly fabricated via top-down methods: starting with a continuous 2D layer, followed by the formation of pores by ion bombardment, electron bombardment or reactive plasma exposure. 9 As evident from a recent review focusing on top-down approaches to fabricate porous 2D membranes, pore densities of 1-10 pores per 100 nm 2 were the highest obtained.…”
Section: Introductionmentioning
confidence: 99%